In the lost lands [videorecording (DVD)] - Martin, George R. R.; Werner, Constantin; Jovovich, Milla; Bautista, David, 1969-; Jover, Arly (Vertical, 2025)
A queen desperate to fulfill her love makes a daring play: she sends the powerful and feared sorceress Gray Alys to the ghostly wilderness of the Lost Lands in search of a magical power, where the sorceress and her guide, the drifter Boyce, must outwit and outfight man and demon.